2008
DOI: 10.1161/atvbaha.108.171538
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Hepatic Metabolism in fld Mice Reveal a Role for Lipin 1 in Regulating VLDL-Triacylglyceride Secretion

Abstract: Objective-Lipin 1 controls fatty acid metabolism in the nucleus as a transcriptional regulator and in the cytosol as an enzyme catalyzing the penultimate step in phosphoglycerol triacylglyceride (TAG) synthesis. We sought to evaluate the effects of lipin 1 on hepatic TAG synthesis and secretion by gain-of-function and loss-of-function approaches. Methods and Results-Rates of TAG synthesis were not impaired in hepatocytes isolated from adult lipin 1-deficient (fld) mice and were actually increased in 14-day-old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
95
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(98 citation statements)
references
References 36 publications
3
95
0
Order By: Relevance
“…These results are consistent with previous findings showing that hepatic LIPIN1 functions as a cytosolic PAP in the regulation of the insulin signaling cascade (4). Recent studies also demonstrated that hepatic LIPIN1 is associated with triglyceride synthesis and secretion, although the results between in vitro and in vivo conditions are somewhat inconsistent (38,39), thereby suggesting that the role of hepatic LIPIN1 appears to involve a cytosolic function related to de novo lipogenesis rather than a nuclear function related to fatty acid oxidation. However, functional differences in hepatic LIPIN1 according to its localization will require further characterization.…”
Section: Discussionsupporting
confidence: 92%
“…These results are consistent with previous findings showing that hepatic LIPIN1 functions as a cytosolic PAP in the regulation of the insulin signaling cascade (4). Recent studies also demonstrated that hepatic LIPIN1 is associated with triglyceride synthesis and secretion, although the results between in vitro and in vivo conditions are somewhat inconsistent (38,39), thereby suggesting that the role of hepatic LIPIN1 appears to involve a cytosolic function related to de novo lipogenesis rather than a nuclear function related to fatty acid oxidation. However, functional differences in hepatic LIPIN1 according to its localization will require further characterization.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with its tissue distribution, lipin-1 contributes the majority of PAP activity in adipose tissue and muscle (6,7). Lipin-1 is also expressed in peripheral nerve, where it is required for normal Schwann cell function (14), and in liver, where it plays a role in response to fasting and in hepatic lipoprotein secretion (5,8,15,16). Mutations in human LPIN1 have recently been detected and cause recurrent acute myoglobinuria in childhood (17), indicating a critical role for lipin-1 in human muscle function.…”
mentioning
confidence: 84%
“…Plasma insulin was measured using the Linco rat/mouse insulin ELISA kits. For determination of plasma radioactivity of [3- Cell Culture Studies-Primary cultures of mouse hepatocytes were prepared as described (29). For isolation of hepatocytes from DIO mice, mice that had been fed a high fat diet for 12 weeks were used.…”
Section: Methodsmentioning
confidence: 99%
“…Plasma insulin and adiponectin concentrations were determined by commercially available ELISAs from Crystal Chemical Co. and Linco Research Inc., respectively. Hepatic triglyceride content was determined using a colorimetric assay as previously described (29).…”
Section: Methodsmentioning
confidence: 99%